2017
DOI: 10.1021/acs.macromol.6b02812
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Polyurethanes as a New Family of Poly(ionic liquid)s for Efficient CO2 Capture

Abstract: Carbon dioxide (CO2) levels are continuously growing, and CO2 is believed to be a significant contributor to global warming and climate change. Therefore, there is a great interest in the development of highly efficient technologies to curb CO2 emissions of current energy sources. In this context to combat such issues, poly­(ionic liquid)­s (PILs) offer an extremely versatile and tunable platform to fabricate a wide variety of sorbents for CO2 capture. To date, the majority of poly­(ionic liquid)­s studied for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
61
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 49 publications
6
61
0
1
Order By: Relevance
“…Existing CO 2 capturem ethods including physicals orbents by porousm aterials, [13][14][15][16] andc hemical sorbents [17] such as aqueous ammonia solution, [18] suffer from variousp roblems. [19][20][21] Compared with conventional solid silica nanofluids, [22,23] porous liquids have better gas capture capacity due to the permanent cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Existing CO 2 capturem ethods including physicals orbents by porousm aterials, [13][14][15][16] andc hemical sorbents [17] such as aqueous ammonia solution, [18] suffer from variousp roblems. [19][20][21] Compared with conventional solid silica nanofluids, [22,23] porous liquids have better gas capture capacity due to the permanent cavities.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In the recent years, polymers containing ionic groups have gained significant attention for various applications in the fields such as gas separation, lithium ion batteries, protonexchange membrane fuel cells (PEMFC), supercapacitors, and so forth. [10][11][12][13][14][15][16][17][18][19][20] It has been demonstrated that polymers containing ionic groups exhibit excellent gas permeation properties and their gas permeation properties can be tuned by varying compositions of ionic groups. 13 For CO 2 separation, polymers containing ionic groups showed high selectivity and high permeability because of interaction of ionic counterpart with CO 2 .…”
mentioning
confidence: 99%
“…[22] Poly(ionic liquids) (PILs), polymers derived from monomers basedo nI Ls,h ave also been investigated for CO 2 capturing. [23][24][25][26] PILs are ionically conductive and their CO 2 adsorption capacity is between 2a nd 20 mg g À1 ,which is higher than their IL counterparts. [2,[27][28][29][30][31] Managing carbon dioxide (CO 2 )r eleased from large-scale industrialp rocesses is of great importance,y et there remain significant technical challenges.H erein, the fabrication of 1mm-thicks olid-state electrochemical devices based on poly-(ionic liquid) ionogels with embedded electrodes capable of both adsorption and electrochemical reduction of CO 2 is reported.T he ionogelsa re prepared via radical polymerization and chemical crosslinking of avinyl imidazolium trifluoromethanesulfonimide ionic liquid monomer in the presence of additional ionic liquids (ILs) that act as swellinga gents and enhance ionic conductivity.…”
Section: Introductionmentioning
confidence: 95%